Polymer-coated silicon-carbon negative electrode material, preparation method thereof and lithium ion battery
By performing carbon coating and polymer coating on the surface of silicon carbon anode material, the problem of silicon carbon anode material due to volume expansion and electrochemical performance decay in lithium-ion batteries is solved, and the high cycle stability and electrochemical performance of the material are improved, extending the service life of the battery.
Patent Information
- Application Number
- CN202510137862.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-11
AI Technical Summary
The existing silicon-carbon anode materials in lithium-ion batteries have short cycle life due to problems such as volume expansion and electrochemical performance decay, making them difficult to meet the needs of high energy density.
By carbon coating and polymer coating on the surface of the silicon carbon substrate, acrylic monomers and specific polymer coating materials are used to form a polymer coating with strong adhesion, conductivity and uniformity to improve the structural stability and conductivity of the material.
It effectively alleviates the volume expansion problem of silicon during charging and discharging, improves the cyclic stability and electrochemical performance of the material, and extends the service life of lithium-ion batteries.
Smart Images

Figure CN119601643A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a polymer-coated silicon-carbon negative electrode material, a preparation method thereof, and a lithium ion battery. Background Art
[0002] The negative electrode material is an important component of the charging and discharging process of lithium-ion batteries. It acts as a carrier of lithium ions and electrons and has the function of storing and releasing energy. Currently, the negative electrode materials of commercial lithium-ion batteries are mainly modified natural graphite and artificial graphite. The preparation technology is relatively mature, but its theoretical specific capacity is only 372mAh / g, which is difficult to meet the demand of the battery application market for high energy density lithium-ion batteries.
[0003] Anode materials with high capacity can effectively improve the energy density of lithium batteries. From the lithium storage mechanism, it can be found that in the graphite anode, 6 carbon atoms are needed to store one lithium ion, while for silicon materials, each silicon atom can be combined with 4 lithium ions. It can be seen that silicon materials have more than 10 times the theoretical capacity of graphite materials. However, due to the large lithium storage capacity of silicon materials, the lattice will expand when lithium is inserted, and the lattice will collapse when lithium is removed, resulting in a huge volume change during the cycle. The silicon particles will be broken and powdered, and thus lose electrical contact with the current collector. And due to the volume effect of silicon materials, the SEI film generated on its surface will continue to grow, continuously consume lithium ions, and cause the capacity to decay rapidly, affecting the electrochemical performance of silicon anode materials in lithium-ion batteries. Silicon-carbon material is a new generation of anode materials with carbon materials as the supporting matrix and silicon particles as the active material. The volume expansion caused by high capacity and the side reaction with the electrolyte accelerate the capacity decay. In actual battery applications, it is still necessary to further improve its performance decay caused by insufficient conductivity and non-negligible volume expansion.
[0004] At present, in order to solve the problems of volume expansion and electrochemical performance degradation faced by silicon-carbon negative electrode materials, surface treatment of silicon-carbon negative electrodes, such as carbon coating, inorganic compound coating and organic polymer coating, can alleviate the adverse effects of volume change on batteries to a certain extent and improve the first reversible capacity, cycle stability and battery rate performance of negative electrode materials.
[0005] For example, in the prior art, patent CN110931744A discloses: a method for preparing a silicon-carbon negative electrode material, by adding an organic monomer and a catalyst to a silicon source, reacting to obtain an organic polymer-coated silicon material, and carbonizing it in an inert gas to obtain a silicon-carbon negative electrode material, which uses low-steric hindrance aldehyde monomers such as formaldehyde and acetaldehyde and phenolic monomers to polymerize and carbonize in a silicon source to form a silicon-carbon negative electrode material with a high-porosity network-like coating structure, which can effectively buffer the volume expansion of silicon during the process of lithium insertion and extraction, and extend the cycle life of lithium-ion batteries.
[0006] However, this method requires the use of a large amount of small molecule monomers such as formaldehyde and acetaldehyde, which are highly toxic and carcinogenic, limiting its industrial application. In addition, the carbon layer formed by the organic polymer after carbonization may not be conductive enough, affecting the conductivity of the electrode material, thereby reducing the rate performance and overall electrochemical performance of the battery. At the same time, the polymerization reaction of adding organic monomers and catalysts and the subsequent carbonization treatment process steps are numerous and the conditions are complex to control, which may increase production costs and difficulties. Moreover, in the actual preparation process, the thickness and uniformity of the coating layer may be difficult to control, resulting in inconsistency in material properties, which in turn affects the stability and consistency of the battery.
[0007] Therefore, the prior art still needs to be improved. Summary of the invention
[0008] In the prior art, the carbon layer formed by the organic polymer in the prior art after carbonization may have insufficient conductivity, affecting the conductivity of the electrode material, thereby reducing the rate performance and overall electrochemical performance of the battery. Therefore, the present invention provides a polymer-coated silicon-carbon negative electrode material and a preparation method thereof and a lithium-ion battery for solving the above problems.
[0009] To achieve the above-mentioned purpose, in a first aspect, the present invention provides a polymer-coated silicon-carbon negative electrode material, which comprises, from the inside to the outside, a silicon-carbon substrate, a carbon coating layer and a polymer coating layer, wherein the polymer coating layer comprises the following materials by mass fraction: 50-98% strong adhesion material, 1-20% conductive material and 1-30% auxiliary material, and the strong adhesion material comprises the following materials by mass fraction: 60-95% acrylic monomer, 1-30% A monomer and 1-30% B monomer, wherein the A monomer is a functional monomer, and the B monomer is a host-guest molecule, and the A monomer comprises at least one of vinyl acetate, acrylonitrile, styrene, 2-acrylamide-2-phenylethanesulfonic acid, hydroxyethyl methacrylate, sodium lignosulfonate, acrylamide and N-vinyl pyrrolidone.
[0010] In one implementation, the acrylic monomer includes any one of acrylic acid, methacrylic acid, methyl methacrylate and 2-hydroxyethyl acrylate.
[0011] In one implementation, the B monomer includes α-cyclodextrin or β-cyclodextrin.
[0012] In one implementation, the silicon carbon substrate includes internal pores and silicon nanoparticles located in the pores, the size of the pores is 0.1-100 nm, and the size of the silicon nanoparticles is 0.1-50 nm.
[0013] In one implementation, the carbon substrate of the silicon-carbon substrate includes any one of porous carbon, natural graphite, artificial graphite mesophase carbon microbeads and expanded graphite.
[0014] In one implementation, the carbon coating layer has a thickness of 1 to 3 nm, and the polymer coating layer has a thickness of 1 to 20 nm.
[0015] In one implementation, the auxiliary material includes a cross-linking agent and a lithium salt, the cross-linking agent includes any one or a combination of at least two of hydroxymethyl cellulose, sulfonated cellulose, carboxymethyl cellulose, polyethylene glycol monomethyl ether, polyethylene glycol monolaurate, polyvinyl alcohol titanate, polyvinyl alcohol formal or locust bean gum; the lithium salt includes lithium hydroxide.
[0016] In a second aspect, the present invention further provides a method for preparing a polymer-coated silicon-carbon negative electrode material, which is used to prepare the above-mentioned polymer-coated silicon-carbon negative electrode material, and comprises the following specific steps: S1. Place the acrylic monomer in a reaction kettle, introduce nitrogen, add the solvent to dissolve, heat to 60-90° C., and add the A monomer and the B monomer dropwise at a uniform speed. After the addition, keep the temperature for 20-60 minutes, then drop the initiator, react for 4-20 hours, and then cool to room temperature to obtain a strong adhesion material; S2, adding a lithium salt solution to the above-mentioned strong adhesive material, stirring for 1 to 3 hours to obtain a lithiated strong adhesive material; taking the lithiated strong adhesive material, conductive material and cross-linking agent in proportion, adding a certain solvent to dissolve and stir, and obtaining a polymer coating material; S3, mixing a porous carbon precursor and a silicon source, burning them under an inert atmosphere to obtain a silicon-carbon substrate, placing the silicon-carbon substrate in a chemical vapor deposition furnace, introducing an inert gas, raising the temperature in the furnace, and then introducing a carbon source gas to obtain a double-shell silicon-carbon composite material intermediate; S4, adding the silicon-carbon material to the polymer coating material, stirring, evaporating the water and then sieving to obtain the polymer-coated silicon-carbon negative electrode material.
[0017] In one implementation, in S1, the initiator includes at least one of ammonium persulfate, azobisisobutyl cyanide and benzoyl peroxide; and the solvent includes deionized water or N-methyl-2-pyrrolidone.
[0018] In a third aspect, the present invention further provides a lithium-ion battery, which comprises the above-mentioned polymer-coated silicon-carbon negative electrode material as a negative electrode.
[0019] Beneficial effects: The present invention effectively alleviates the mechanical stress problem caused by the volume expansion of silicon during the charging and discharging process by carbon coating and polymer coating on the surface of the silicon-carbon substrate, thereby improving the cycle stability of the material; by using acrylic monomers and specific polymer coating materials, the silicon-carbon material is coated more stably and efficiently, which can improve the structural stability, conductivity and uniformity of the material, thereby improving the overall performance and service life of the lithium-ion battery; combining high-adhesion polymers, conductive materials and auxiliary materials to achieve the comprehensive performance of high capacity, high conductivity and high cycle stability; the present invention effectively solves the problems of volume expansion and short cycle life faced by traditional silicon-carbon negative electrode materials in applications, and has high practical value and potential market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a flow chart of the steps of the method for preparing the polymer-coated silicon-carbon negative electrode material provided by the present invention.
[0021] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0023] Read more Figure 1 , Figure 1It is a flow chart of the steps of the preparation method of the polymer-coated silicon-carbon negative electrode material provided by the present invention. The present invention provides a polymer-coated silicon-carbon negative electrode material, which includes a silicon-carbon substrate, a carbon coating layer and a polymer coating layer from the inside to the outside, and the polymer coating layer includes the following materials by mass fraction: 50~98% strong adhesion material, 1~20% conductive material and 1~30% auxiliary material, and the strong adhesion material includes the following materials by mass fraction copolymerized: 60~95% acrylic monomer, 1~30% A monomer and 1~30% B monomer. Among them, the A monomer is a functional monomer, which is used to enhance the adhesion, mechanical properties and chemical stability of the material. The B monomer is a host-guest type molecule, which is used for molecular-level regulation, inclusion and enhanced interface compatibility.
[0024] Specifically, the acrylic monomer includes any one of acrylic acid, methacrylic acid, methyl methacrylate and 2-hydroxyethyl acrylate. The A monomer is a functional monomer, and the B monomer is a host-guest molecule. The A monomer includes at least one of vinyl acetate, acrylonitrile, styrene, 2-acrylamide-2-phenylethanesulfonic acid, hydroxyethyl methacrylate, sodium lignosulfonate, acrylamide and N-vinyl pyrrolidone. The B monomer includes α-cyclodextrin or β-cyclodextrin.
[0025] Specifically, the conductive material includes at least one of graphene, acetylene black, carbon black, nanocellulose, single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0026] The auxiliary material includes a cross-linking agent and a lithium salt. The cross-linking agent includes any one of hydroxymethyl cellulose, sulfonated cellulose, carboxymethyl cellulose, polyethylene glycol monomethyl ether, polyethylene glycol monolaurate, polyvinyl alcohol titanate, polyvinyl alcohol formal or locust bean gum, or a combination of at least two thereof. The lithium salt includes lithium hydroxide.
[0027] Specifically, the silicon-carbon substrate includes internal pores and silicon nanoparticles located in the pores, the size of the pores is 0.1~100nm, and the size of the silicon nanoparticles is 0.1~50nm. The carbon substrate of the silicon-carbon substrate includes any one of porous carbon, natural graphite, artificial graphite mesophase carbon microspheres and expanded graphite, and the particle size D50 value of the carbon substrate is 5~10μm. Further, the silicon nanoparticles are deposited on the carbon substrate by vapor deposition, and in order to prevent oxidation of nano-silicon and reduce the specific surface, carbon coating is also performed on the silicon-carbon substrate by vapor deposition. The thickness of the carbon coating layer is 1~3nm, and the thickness of the polymer coating layer is 1~20nm.
[0028] The present invention also provides a method for preparing a polymer-coated silicon-carbon negative electrode material, which is used to prepare the above-mentioned polymer-coated silicon-carbon negative electrode material, and comprises the following specific steps: S1. Place the acrylic monomer in a reaction kettle, introduce nitrogen, add the solvent to dissolve, heat to 60-90° C., and add the A monomer and the B monomer dropwise at a uniform speed. After the addition, keep the temperature for 20-60 minutes, then drop the initiator, react for 4-20 hours, and then cool to room temperature to obtain a strong adhesion material; S2, adding a lithium salt solution to the above-mentioned strong adhesive material, stirring for 1 to 3 hours to obtain a lithiated strong adhesive material; taking the lithiated strong adhesive material, conductive material and cross-linking agent in proportion, adding a certain solvent to dissolve and stir, and obtaining a polymer coating material; S3, mixing a porous carbon precursor and a silicon source, burning them under an inert atmosphere to obtain a silicon-carbon substrate, placing the silicon-carbon substrate in a chemical vapor deposition furnace, introducing an inert gas, raising the temperature in the furnace, and then introducing a carbon source gas to obtain a double-shell silicon-carbon composite material intermediate; S4, adding the silicon-carbon material to the polymer coating material, stirring, evaporating the water and then sieving to obtain the polymer-coated silicon-carbon negative electrode material.
[0029] Specifically, in S1, the initiator includes at least one of ammonium persulfate, azobisisobutyl cyanide and benzoyl peroxide; the solvent includes deionized water or N-methyl-2-pyrrolidone (NMP). The reaction in this step is carried out under a protective atmosphere, the reaction temperature is 60-90°C, and the reaction time is 4-20 hours.
[0030] In S2, the solution needs to be stirred until the pH value is weakly alkaline, so that a strongly adhesive material after lithiation is obtained.
[0031] In S3, it specifically includes: adding a carbon source into a chemical vapor deposition furnace, introducing an inert gas, maintaining for 60 minutes, then adjusting the temperature in the furnace for burning, and introducing a silicon source gas to obtain a silicon-carbon substrate.
[0032] The flow rate of the inert gas is 1-20 L / min. The inert gas includes any one of nitrogen, argon and hydrogen. The calcination temperature is 400-700°C, for example, the calcination temperature is 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C. The flow rate of the silicon source gas is 0.5-10 L / min, the time for passing the silicon source gas is 100-800 min, and the silicon source gas is any one of monosilane, disilane and silane derivatives.
[0033] The specific steps of forming a carbon coating layer on the surface of a silicon-carbon substrate include: placing a silicon-carbon substrate in a chemical vapor deposition furnace, introducing an inert gas, raising the temperature in the furnace, and then introducing a carbon source gas to obtain a double-shell silicon-carbon composite intermediate. The flow rate of the inert gas is 1 to 20 L / min, for example, the flow rate of the inert gas is 1 L / min, 5 L / min, 10 L / min, 15 L / min or 20 L / min. The inert gas includes any one of nitrogen, argon and hydrogen. The final temperature of the furnace temperature is 500 to 800 ° C, for example, the furnace temperature is raised to 500 ° C, 550 ° C, 600 ° C, 650 ° C, 700 ° C, 750 ° C or 800 ° C. The speed of introducing the carbon source gas is 1-10 L / min, for example, the speed of introducing the carbon source gas is 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min or 10 L / min. The time of introducing the carbon source gas is 50-500 min, for example, the time of introducing the carbon source gas is 50 min, 100 min, 150 min, 200 min, 250 min, 300 min, 350 min, 400 min, 450 min or 500 min. The carbon source gas includes any one of acetylene, ethylene, ethylene and methane.
[0034] The present invention further illustrates the technical solution of the present invention through the following examples and comparative examples.
[0035] Embodiment 1: This embodiment provides a method for preparing a polymer-coated silicon-carbon negative electrode material, which is used to prepare the above-mentioned polymer-coated silicon-carbon negative electrode material, and includes the following specific steps: S1. Place 8 g of acrylic acid in a reactor, introduce nitrogen, add 300 g of deionized water to dissolve, set the stirring speed to 500 rpm, raise the temperature to 80°C, add 2-acrylamide-2-phenylethanesulfonic acid and β-cyclodextrin and mix them evenly, add dropwise at a uniform speed, set the dropping time to 15 min, keep warm at 80°C for 20 min after the addition, then add 0.05 g of ammonium persulfate initiator, react for 8 h, and then cool to room temperature to obtain the strong adhesion material.
[0036] S2. Preparation of polymer coated material: Add 3.5 g of lithium hydroxide aqueous solution to the strong adhesion material prepared in S1, stir at 500 rpm for 2 h, test the pH to be 7.5, which is weakly alkaline, to obtain the lithiated strong adhesion material, take 4.0 g of the lithiated strong adhesion material, 0.4 g of graphene and 0.6 g of polyethylene glycol monolaurate, dissolve them in 200 g of water, stir at 2000 rpm for 1 h, and obtain the polymer coated material.
[0037] S3. Preparation of silicon-carbon material: Add 1500g of porous carbon to the CVD furnace, introduce nitrogen at a flow rate of 14L / min, and maintain for 60 minutes. Raise the temperature in the CVD furnace to 520°C, introduce monosilane at a flow rate of 3L / min, and continue to introduce it for 500min to obtain a silicon-carbon substrate. Add the obtained silicon-carbon substrate to the CVD furnace, and introduce nitrogen at a flow rate of 14L / min. Raise the temperature in the CVD furnace to 550°C, introduce acetylene gas at a flow rate of 3L / min, and continue to introduce it for 200min to obtain a double-shell silicon-carbon composite material intermediate.
[0038] S4. Preparation of polymer-coated silicon-carbon negative electrode material: 150 g of the silicon-carbon material prepared in S3 was added to the polymer-coated material prepared in S2, stirred at 2000 rpm for 1 hour, and then dried at 120°C for 12 hours to evaporate water, and then the dried product was sieved through a 400-mesh screen to obtain the polymer-coated silicon-carbon negative electrode material.
[0039] Embodiment 2: This embodiment provides a method for preparing a polymer-coated silicon-carbon negative electrode material, which is used to prepare the above-mentioned polymer-coated silicon-carbon negative electrode material, and includes the following specific steps: S1. Place 8 g of acrylic acid in a reactor, introduce nitrogen, add 300 g of NMP to dissolve, set the stirring speed to 500 rpm, raise the temperature to 80°C, add 2-acrylamide-2-phenylethanesulfonic acid and β-cyclodextrin and mix them evenly, add dropwise at a uniform speed, set the dropping time to 15 min, keep warm at 80°C for 20 min after the addition, then add 0.05 g of ammonium persulfate initiator, react for 8 h, and then cool to room temperature to obtain the strong adhesion material.
[0040] S2. Preparation of polymer coated material: Add 3.5 g of lithium hydroxide solution to the strong adhesion material prepared in S1, stir at 500 rpm for 2 h, test the pH to be 7.5, which is weakly alkaline, to obtain the lithiated strong adhesion material, take 4.0 g of the lithiated strong adhesion material, 0.4 g of graphene and 0.6 g of polyethylene glycol monolaurate, dissolve them in 200 g of NMP, stir at 2000 rpm for 1 h, and obtain the polymer coated material.
[0041] The specific steps of S3 and S4 are the same as those in Example 1 and will not be repeated here.
[0042] Example 3 In this embodiment, the 2-acrylamide-2-phenylethanesulfonic acid in Example 1 is replaced by vinyl acetate, and the other specific steps are the same as those in Example 1, which will not be repeated here.
[0043] Example 4 In this example, the 2-acrylamide-2-phenylethanesulfonic acid in Example 1 is replaced by N-vinyl pyrrolidone, and the other specific steps are the same as those in Example 1, which will not be repeated here.
[0044] Comparative Example 1: This comparative example provides a silicon-carbon negative electrode material obtained by depositing silicon on a porous carbon material and then coating it with carbon. The specific steps include: adding 1500g of porous carbon to a CVD furnace, introducing nitrogen at a flow rate of 14L / min, and maintaining it for 60 minutes. Raise the temperature in the CVD furnace to 520°C, introduce monosilane at a flow rate of 3L / min, and continue to introduce it for 500min to obtain a silicon-carbon substrate. Add the obtained silicon-carbon substrate to a CVD furnace, and introduce nitrogen at a flow rate of 14L / min. Raise the temperature in the CVD furnace to 550°C, introduce acetylene gas at a flow rate of 3L / min, and continue to introduce it for 200min to obtain a double-shell silicon-carbon composite material.
[0045] Comparative Example 2: Compared with Example 1, in this comparative example, 2-acrylamide-2-phenylethanesulfonic acid and β-cyclodextrin are not added to S1, and other specific steps are the same as those in Example 1, which will not be repeated here.
[0046] Comparative Example 3: Compared with Example 1, in this comparative example, 2-acrylamide-2-phenylethanesulfonic acid is not added to S1, and other specific steps are the same as those in Example 1, which will not be repeated here.
[0047] Comparative Example 4: Compared with Example 1, in this comparative example, β-cyclodextrin is not added to S1, and other specific steps are the same as those in Example 1, which will not be repeated here.
[0048] Electrochemical performance test: The silicon-carbon negative electrode material, acetylene black and LA133 adhesive obtained above were prepared into a uniform slurry in a ratio of 80:10:10, and the slurry was coated on a copper foil, dried, and assembled into button cells after punching, wherein the counter electrode was a metal lithium sheet, the electrolyte was a general lithium-ion battery electrolyte, the current of the charge and discharge test was 300 mA / g, and the measured results are shown in Table 1.
[0049] Table 1. Electrochemical performance test results of various embodiments and comparative examples It can be seen from Table 1 that the first lithium insertion capacity of Examples 1 to 4 is significantly higher than that of Comparative Examples 1 to 4, indicating that the use of functional coating materials (lithiated strong adhesion materials combined with graphene and polyethylene glycol monolaurate) can significantly improve the specific capacity of silicon-carbon negative electrode materials. In the embodiments, the interface stability of the silicon-carbon negative electrode is enhanced by polymer coating (such as acrylic acid-based polymer), the silicon expansion effect is effectively suppressed, and the irreversible side reactions during the first lithium insertion are reduced; the 2-acrylamide-2-phenylethanesulfonic acid and β-cyclodextrin introduced in the embodiments provide adhesion and uniform coating ability, and enhance the mechanical stability and interface integrity of the material; in Comparative Example 2 (without 2-acrylamide-2-phenylethanesulfonic acid) and Comparative Example 4 (without β-cyclodextrin), the first capacity and cycle capacity are significantly reduced, indicating that monomer A and monomer B play a key role in performance improvement. In Comparative Example 1, a double-shell silicon-carbon negative electrode material was prepared only by the CVD method, but no polymer coating was introduced. Although its first lithium insertion capacity was high, its first efficiency and cycle performance were poor, indicating that there were many side reactions on the interface and the active material fell off seriously, making it impossible to use stably for a long time. The embodiment achieves a balance between capacity, efficiency and cycle performance through adhesive materials (such as 2-acrylamide-2-phenylethanesulfonic acid, β-cyclodextrin), conductive additives (graphene) and lithiation treatment. Although the replacement of key components (such as vinyl acetate and N-vinyl pyrrolidone) still has good performance, the performance is slightly lower than the original formula (Example 1), which further illustrates the significant effect of specific adhesive materials on performance optimization. The above data show that the application of functional coating materials in silicon-carbon negative electrode materials significantly improves the electrochemical performance, including higher first lithium insertion capacity, first efficiency and cycle stability.
[0050] In summary, the present invention effectively alleviates the mechanical stress problem caused by the volume expansion of silicon during the charging and discharging process by carbon coating and polymer coating on the surface of the silicon-carbon substrate, thereby improving the cycle stability of the material; by using acrylic monomers and specific polymer coating materials, the silicon-carbon material is coated more stably and efficiently, which can improve the structural stability, conductivity and uniformity of the material, thereby improving the overall performance and service life of the lithium-ion battery; combined with high-adhesion polymers, conductive materials and auxiliary materials, the comprehensive performance of high capacity, high conductivity and high cycle stability is achieved; the present invention effectively solves the problems of volume expansion and short cycle life faced by traditional silicon-carbon negative electrode materials in applications, and has high practical value and potential market application prospects.
[0051] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A polymer-coated silicon-carbon negative electrode material, characterized in that: From the inside to the outside, it includes a silicon-carbon substrate, a carbon coating layer and a polymer coating layer, wherein the polymer coating layer includes the following materials by mass fraction: 50-98% strong adhesion material, 1-20% conductive material and 1-30% auxiliary material, and the strong adhesion material includes the following materials by mass fraction copolymerized: 60-95% acrylic monomer, 1-30% A monomer and 1-30% B monomer, wherein the A monomer is a functional monomer, and the B monomer is a host-guest molecule, and the A monomer includes at least one of vinyl acetate, acrylonitrile, styrene, 2-acrylamide-2-phenylethanesulfonic acid, hydroxyethyl methacrylate, sodium lignosulfonate, acrylamide and N-vinyl pyrrolidone.
2. The polymer-coated silicon-carbon negative electrode material according to claim 1, characterized in that: The acrylic monomer includes any one of acrylic acid, methacrylic acid, methyl methacrylate and 2-hydroxyethyl acrylate.
3. The polymer-coated silicon-carbon negative electrode material according to claim 1, characterized in that: The B monomer includes α-cyclodextrin or β-cyclodextrin.
4. The polymer-coated silicon-carbon negative electrode material according to claim 1, characterized in that: The silicon carbon substrate comprises internal pores and silicon nanoparticles located in the pores. The size of the pores is 0.1-100 nm, and the size of the silicon nanoparticles is 0.1-50 nm.
5. The polymer-coated silicon-carbon negative electrode material according to claim 1, characterized in that: The carbon substrate of the silicon-carbon substrate includes any one of porous carbon, natural graphite, artificial graphite mesophase carbon microspheres and expanded graphite.
6. The polymer-coated silicon-carbon negative electrode material according to claim 1, characterized in that: The thickness of the carbon coating layer is 1-3 nm, and the thickness of the polymer coating layer is 1-20 nm.
7. The polymer-coated silicon-carbon negative electrode material according to claim 1, characterized in that: The auxiliary material includes a cross-linking agent and a lithium salt. The cross-linking agent includes any one of hydroxymethyl cellulose, sulfonated cellulose, carboxymethyl cellulose, polyethylene glycol monomethyl ether, polyethylene glycol monolaurate, polyvinyl alcohol titanate, polyvinyl alcohol formal or locust bean gum, or a combination of at least two thereof. The lithium salt includes lithium hydroxide.
8. A method for preparing a polymer-coated silicon-carbon negative electrode material, characterized in that: It is used to prepare the polymer-coated silicon-carbon negative electrode material according to any one of claims 1 to 7, and comprises the following specific steps: S1. Place the acrylic monomer in a reaction kettle, introduce nitrogen, add the solvent to dissolve, heat to 60-90° C., and add the A monomer and the B monomer dropwise at a uniform speed. After the addition, keep the temperature for 20-60 minutes, then drop the initiator, react for 4-20 hours, and then cool to room temperature to obtain a strong adhesion material; S2, adding a lithium salt solution to the above-mentioned strong adhesive material, stirring for 1 to 3 hours to obtain a lithiated strong adhesive material; taking the lithiated strong adhesive material, conductive material and cross-linking agent in proportion, adding a certain solvent to dissolve and stir, and obtaining a polymer coating material; S3, mixing a porous carbon precursor and a silicon source, burning them under an inert atmosphere to obtain a silicon-carbon substrate, placing the silicon-carbon substrate in a chemical vapor deposition furnace, introducing an inert gas, raising the temperature in the furnace, and then introducing a carbon source gas to obtain a double-shell silicon-carbon composite material intermediate; S4, adding the silicon-carbon material to the polymer coating material, stirring, evaporating the water and then sieving to obtain the polymer-coated silicon-carbon negative electrode material.
9. The method for preparing a polymer-coated silicon-carbon negative electrode material according to claim 8, characterized in that: In S1, the initiator includes at least one of ammonium persulfate, azobisisobutyl cyanide and benzoyl peroxide; and the solvent includes deionized water or N-methyl-2-pyrrolidone.
10. A lithium ion battery, characterized in that: The invention comprises the polymer-coated silicon-carbon negative electrode material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Silicon-carbon negative electrode material and preparation method thereof
CN110931744A
Composite binder applied to silicon-carbon negative electrode system of lithium ion battery and negative electrode material containing binder
CN115588742A
Silicon-based negative electrode material and preparation method and application thereof
CN116544385A
Double-shell silicon-carbon composite material, preparation method thereof and lithium ion battery
CN118507668A
Silicon-carbon negative electrode material and preparation method and application thereof
CN118888702A
Cited By
Composite silicon-carbon negative electrode material and preparation method thereof
CN122417832A